2016
DOI: 10.1093/eurheartj/ehv689
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical stress in coronary atherosclerosis: emerging insights from computational modelling

Abstract: Coronary plaque rupture is the most common cause of vessel thrombosis and acute coronary syndrome. The accurate early detection of plaques prone to rupture may allow prospective, preventative treatment; however, current diagnostic methods remain inadequate to detect these lesions. Established imaging features indicating vulnerability do not confer adequate specificity for symptomatic rupture. Similarly, even though experimental and computational studies have underscored the importance of endothelial shear stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 135 publications
2
80
0
5
Order By: Relevance
“…The local flow alterations, especially the low ESS pattern corresponding to the vessel geometry change might mediate biological responses through increased thrombogenicity and impaired rate of vascular repair . In addition, low ESS promotes smooth muscle cell (SMC) proliferation and migration, the expression of proteins that perpetuate inflammation and lipid accumulation and can transform the benign neointima to a vulnerable plaque . Therefore, stented lesions that are exposed to low ESS exhibit augmented neoatherosclerosis and neointimal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The local flow alterations, especially the low ESS pattern corresponding to the vessel geometry change might mediate biological responses through increased thrombogenicity and impaired rate of vascular repair . In addition, low ESS promotes smooth muscle cell (SMC) proliferation and migration, the expression of proteins that perpetuate inflammation and lipid accumulation and can transform the benign neointima to a vulnerable plaque . Therefore, stented lesions that are exposed to low ESS exhibit augmented neoatherosclerosis and neointimal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…whereas the inner regions have a lower ESS [22]. [27][28][29]. Therefore, stented lesions that are exposed to low ESS exhibit augmented neoatherosclerosis and neointimal hyperplasia.…”
Section: The Geometrical Coronary Changes After Stenting and Stent mentioning
confidence: 99%
“…11 The unsteady nature of arterial blood flow determines the endothelial shear stress in combination with the geometric vessel configuration, being characterized by direction and magnitude. In regions with irregular geometry, a disturbed laminar flow appears, and the pulsatile flow shows oscillatory endothelial shear stress.…”
Section: Shear Stressmentioning
confidence: 99%
“…Numerous histology and in vivo studies have shown that local haemodynamic forces and in particular the endothelial shear stress (ESS) are instigators of plaque formation and of the development of high-risk vulnerable plaques 1. Clinical reports have explored the implications of plaque morphology and of ESS on atherosclerotic disease progression,2 and experimental studies have examined the effect of ESS in lesions with a high-risk phenotype3; however, there is limited clinical data about the implications of ESS on the dynamic changes in plaque phenotype.…”
Section: Introductionmentioning
confidence: 99%